PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PELABUHAN INDONESIA (Persero) CABANG SIBOLGA (Jurnal Ekonomi Bisnis dan Akuntansi, 2022)
Pelabuhan Indonesia (Persero) Sibolga Branch is one of the companies engaged in port services. As a Persero, the shareholder is in the hands of the Government, in this case represented by the Minister of Finance of the Republic of Indonesia. This study aims to determine the influence of organizational culture and work environment on employee performance at PT. Pelabuhan Indonesia (Persero) Sibolga Branch. This type of research is research that analyzes causal relationships (influence) between variables in research. The approach used in this research is a quantitative approach. The population is employees . PT. Pelabuhan Indonesia (Persero) Sibolga Branch with a total of 47 employees, namely 11 organic employees and 36 non-organic employees. The data collection technique used was a questionnaire. From the SPSS processing results, it was obtained that there was a relationship between Organizational Culture (X1) and Employee Performance of 0.617 and a relationship between Work Environment (X2) and Employee Performance of 0.684. It is known that there is a positive relationship and the intended category is sufficient. From the results of the coefficient of discrimination obtained by 0.494, this means that what occurs in the variation of the dependent variable (Employee Performance) of 49.9% is determined by the independent variable Organizational Culture (X1) and Work Environment (X2). The results show that the influence of organizational culture on employee performance is not significant, while the work environment variables have a significant effect, and the influence of organizational culture and work environment on employee performance has a significant effect on employee performance at PT. Pelabuhan Indonesia (Persero) Sibolga Branch.